2002
DOI: 10.1093/intimm/dxf070
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural analysis of the panallergen profilin B cell epitopes defined by monoclonal antibodies

Abstract: Interactions of five mouse mAb (10A4, 5F2, 9A7, 9G4 and 3H8) and sunflower profilin were characterized using synthetic overlapping peptides. All the continuous B cell epitopes analyzed in this work were 6-10 amino acids in length, and clustered at the N- and C-terminal alpha-helices and a two-stranded segment composed of residues 40-50. Mutational analysis of the epitopes revealed that single amino acid changes within these peptides had dramatic effects on IgG-binding characteristics. A three-dimensional molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…In contrast, B-cell epitopes are either linear or conformational and are located on the surface of the molecule accessible to antibodies. The extension of the epitope may range from 5 to 8 (or even more) amino acids for IgE to be able of binding to the epitope [60][61][62][63]. However, we have found linear B-cell epitopes in lupin β-conglutins and the other legume allergens with a wide range of amino acid lengths, and overlapping with conformational epitopes.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, B-cell epitopes are either linear or conformational and are located on the surface of the molecule accessible to antibodies. The extension of the epitope may range from 5 to 8 (or even more) amino acids for IgE to be able of binding to the epitope [60][61][62][63]. However, we have found linear B-cell epitopes in lupin β-conglutins and the other legume allergens with a wide range of amino acid lengths, and overlapping with conformational epitopes.…”
Section: Discussionmentioning
confidence: 76%
“…For Cuc m 2 and Hel a 2 (profilin from sunflower pollen), it was experimentally demonstrated that the IgE biding epitopes overlap significantly with areas of the molecules participating in formation of the protein⅐protein complexes (Fig. 9, C and D) (43,44). The residues forming these epitopes in Cuc m 2 and Hel a 2 are also highly conserved in Amb a 8, Art v 4, and Bet v 2.…”
Section: Discussionmentioning
confidence: 98%
“…D, epitopes identified in Hel a 2.0101. The epitopes are labeled using a convention used in the original paper reporting these epitopes (43).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the location and characterization of IgE epitopes on profilins [46,47,48]. Fedorov et al [49] mapped Bet v 2 IgE epitopes on the N- and C-terminal α-helices and on a segment of the protein containing two strands of the β-sheet.…”
Section: Profilin: the Etiology Of Cross-reactivitymentioning
confidence: 99%